Bulan Ramadan dan Kebahagiaan Seorang Muslim - Royanulloh Royanulloh; Komari Komari (Jurnal Psikologi Islam dan Budaya, 2019)
The Islamic and the Nusantara tradition shows that Ramadan is always welcomed with joy. Therefore, Ramadan is related to happiness. This quantitative research analyzes how changes in happiness occur as the coming of Ramadan. The respondents are 117 muslims adult who have received pesantren education. The results showed that significant differences in positive emotions between weeks 3, 2, and 1 before the coming of Ramadan. Meanwhile, negative emotions did not show a significant decrease. Then, the correlation test results show there is a positive correlation between the arrival of Ramadan with positive emotions. Meanwhile, the correlation test was negative with negative emotions. This research proves the coming of the month of Ramadan associated with increasing happiness of a muslim.